Bibliometric analysis of the flipped classroom pedagogical model: Trends and strategic lines of study - del Arco, Isabel; Mercadé-Melé, Pere; Ramos-Pla, Anabel; Flores-Alarcia, Òscar (Frontiers in Education, 2022)
The Flipped Classroom (FC) emerged at the beginning of the 20th century as an alternative pedagogical model to the traditional classroom. It consists of inverting (flipping) some teaching-learning procedures, transferring some activities outside the classroom and reformulating the roles of the teacher and the student. The aim of this study is to identify the main existing trends and emerging strategic lines of research with respect to the FC pedagogical model. To this end, a bibliometric study was carried out by analyzing the international scientific production found in the Web of Science (WoS) database. A total of 2,194 articles were reviewed during the period from 2007 to 2021. The results showed an increase in publications on FC from 2013 onwards, reaching a significant peak in the scientific literature in the last two years. Scientific evidence is presented on the didactic virtue of the model, together with the increase in the degree of student satisfaction and motivation. New lines for the future are suggested, such as: providing evidence of the improvement in academic performance and solid and profound learning results in its application to different fields of knowledge, educational contexts, or with different types of students. Also, to investigate the co-responsibility of students by stimulating autonomy and self-regulation